Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.1 Properties of Functions - 2.1 Exercises - Page 55: 46



Work Step by Step

$f(2-r)=$ ... substitute x with $(2-r)$ and simplify $=6(2-r)^{2}-2$ $=6(4-4r+r^{2})-2$ $=24-24r+6r^{2}-2$ $=6r^{2}-24r+22$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.